2015
DOI: 10.1161/atvbaha.114.304326
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein Estrogen Receptor as a Regulator of Low-Density Lipoprotein Cholesterol Metabolism

Abstract: T he importance of estrogen as a regulator of plasma lipid metabolism has been most clearly demonstrated in settings of estrogen deficiency (eg, menopause). Bilateral ovariectomy in premenopausal women causes an increase in plasma levels of low-density lipoprotein (LDL) when compared with premenopausal women with preserved ovaries.1 Furthermore, LDL cholesterol levels increase after onset of menopause. 2Multiple mechanisms have been proposed by which estrogens regulate lipoprotein metabolism in humans, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 59 publications
2
49
0
1
Order By: Relevance
“…In a complementary set of experiments, these investigators elegantly demonstrated that chronic administration of G1 to ovariectomized GPER+/+ mice inhibited atherosclerosis and vascular inflammation without any measurable uterotrophic activity. A further interesting development in the role of GPER in atherosclerosis may be realized from the recent finding from a genome wide association study that demonstrated a direct genetic and pharmacological linkage between GPER and serum LDL receptor levels via a decrease in proprotein convertase subtilisin kexin type 9 (PCSK9) expression [Hussain et al, 2015]. Collectively, these data suggest a critical role for GPER-1 in anti-atherogenesis and the reduction of cardiovascular disease.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In a complementary set of experiments, these investigators elegantly demonstrated that chronic administration of G1 to ovariectomized GPER+/+ mice inhibited atherosclerosis and vascular inflammation without any measurable uterotrophic activity. A further interesting development in the role of GPER in atherosclerosis may be realized from the recent finding from a genome wide association study that demonstrated a direct genetic and pharmacological linkage between GPER and serum LDL receptor levels via a decrease in proprotein convertase subtilisin kexin type 9 (PCSK9) expression [Hussain et al, 2015]. Collectively, these data suggest a critical role for GPER-1 in anti-atherogenesis and the reduction of cardiovascular disease.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Dyslipidemia in male GPER KO1 mice, as evidenced by increased serum levels of total cholesterol, LDL cholesterol and triglycerides, occurred as the mice aged (24 vs. 12 months) [101]; whereas in young female GPER KO1 mice, an atherogenic diet resulted in increased total and LDL cholesterol levels [124]. Consistent with these observations in mice, epidemiological evidence for the regulation of LDL cholesterol through GPER activity in humans derives from carriers of a hypofunctional GPER polymorphism that correlates with higher circulating levels of plasma LDL cholesterol, potentially through the regulation of LDL receptor expression in the liver [138]. …”
Section: Metabolic Functions: Obesity and Diabetesmentioning
confidence: 98%
“…Studying the variant Y157C in a PAR4 expression construct, they found reduced PAR4 responses because of aberrant anterograde surface receptor trafficking, which validated the involvement of rare F2RL3 variants in altering PAR4 reactivity after treatment with therapeutic PAR1 antagonists. 19 In another study, Hussain et al 20 considered the unknown link between estrogen deficiency and increased LDL-C (low-density lipoprotein cholesterol). They analyzed the role of GPER (G-protein estrogen receptor) in the regulation of both the LDL receptor and PCSK9 (proprotein convertase subtilisin kexin type 9).…”
Section: The Post-gwas Era: Functional Validation Of Snps Associated mentioning
confidence: 99%
“…Taken together, these results suggest a role of GPER in LDL metabolism. 20 Additional studies pursued functional assessment of GWAS-identified SNPs, notably in relation to CAD. For instance, 1 group functionally investigated a coding variant, rs1051338, in LIPA, encoding lysosomal acid lipase and found that the risk allele leads to faster lysosomal acid lipase degradation, reduced protein levels, and decreased activity.…”
Section: The Post-gwas Era: Functional Validation Of Snps Associated mentioning
confidence: 99%